A Pragma-Stylistic Analysis of Reflections on Death and the Construction of Character Education Values in the Poem Ayā Man Yadda'ī al-Fahm - Aulia, Jihan; Sopian, Asep; Aqwam, Sena Zaeni (Study Program of Arabic Language Teaching, 2025)
This study aims to identify the forms of imagery, language style, and pragmatic implications in several selected Arabic verses, and to explain the construction of character education values that emerge through the analysis. This research is a qualitative study that employs a content analysis approach. The technique used in this research is documentation. The primary main text is the classic p